Land Cover Map 2007 (1km dominant aggregate class, GB) v1.2 - Morton, R.D.; Rowland, C.S.; Wood, C.M.; Meek, L.; Marston, C.G.; Smith, G.M. (NERC Environmental Information Data Centre, 2014)
This dataset consists of a 1km resolution raster version of the Land Cover Map 2007 for Great Britain. Each 1km pixel represents the dominant aggregate class across the 1km area. The aggregate classes are aggregations of the target classes, broadly representing Broad Habitats (see below). The dataset is part of a series of data products produced by the Centre for Ecology & Hydrology known as LCM2007. LCM2007 is a parcel-based thematic classification of satellite image data covering the entire United Kingdom. The map updates and upgrades the Land Cover Map of Great Britain (LCMGB) 1990 and LCM2000. Like the earlier 1990 and 2000 products, LCM2007 is derived from a computer classification of satellite scenes obtained mainly from Landsat, IRS and SPOT sensors and also incorporates information derived from other ancillary datasets. LCM2007 was classified using a nomenclature corresponding to the Joint Nature Conservation Committee (JNCC) Broad Habitats, which encompasses the entire range of UK habitats. In addition, it recorded further detail where possible. The series of LCM2007 products includes vector and raster formats, with a number of different versions containing varying levels of detail and at different spatial resolutions.
LCM2007 uses a spatial framework based on OS MasterMap (R). MasterMap was generalised to remove unnecessary detail, then the framework was segmented according to the underlying satellite data to split areas of non-uniform landscape. The data was classified according to a parcel-based supervised maximum likelihood classification procedure. The raster products are derived from the vector products. Version 1.2 includes OS tiles NW and HZ, and also a water class. Refer to supporting documentation for further information.
Keywords: Great Britain; England; Scotland; Wales; Monitoring & Observing Systems; Land cover; Parr Section